SOSIALISASI PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN BUAH NANAS MENJADI PINEAPPLE CHUNKS DI DESA ALAI - Ahmad Darmawan; Lukita Tripermata; Roswaty (Politeknik Negeri Sriwijaya, 2022)
Alai Village which is located in Lembak District, Muara Enim Regency is an area that has considerable potential in producing pineapples, but has not been utilized optimally by farmers, most of the pineapples produced are directly sold raw without being processed by them. The processing of pineapples packaged in plastic zippers is intended to extend the shelf life of the fruit, maintain the nutritional value, and increase the economic value of the fruit. With this processing empowerment, it is hoped that it can help improve the village economy and utilize pineapple raw materials that are more durable to bring up various innovations of processed pineapple in a sustainable manner.